2012
DOI: 10.1371/journal.pone.0044562
|View full text |Cite|
|
Sign up to set email alerts
|

The Dose–Response Decrease in Heart Rate Variability: Any Association with the Metabolites of Polycyclic Aromatic Hydrocarbons in Coke Oven Workers?

Abstract: BackgroundAir pollution has been associated with an increased risk of cardiopulmonary mortality and decreased heart rate variability (HRV). However, it is unclear whether coke oven emissions (COEs) and polycyclic aromatic hydrocarbons (PAHs) are associated with HRV.ObjectivesOur goal in the present study was to investigate the association of exposure to COEs and the urinary metabolite profiles of PAHs with HRV of coke oven workers.MethodsWe measured benzene soluble matter, carbon monoxide, sulfur dioxide, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…PAH metabolites have been reported to be associated with reduced heart rate variability, a predictor of adverse cardiovascular effects such as hypertension, coronary artery disease, myocardial infarction etc. in coke oven workers [43]. The association of high levels of PAH metabolites with C-reactive protein [44] points that metabolites may aid in the progression of atherosclerosis through inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…PAH metabolites have been reported to be associated with reduced heart rate variability, a predictor of adverse cardiovascular effects such as hypertension, coronary artery disease, myocardial infarction etc. in coke oven workers [43]. The association of high levels of PAH metabolites with C-reactive protein [44] points that metabolites may aid in the progression of atherosclerosis through inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive spectrum of 12 PAHs metabolites, including 1-hydroxynaphthalene, 2-hydroxynaphthalene, 2-hydroxyfluorene, 9-hydroxyfluorene, 1-hydroxyphenanthrene, 2-hydroxyphenanthrene, 3-hydroxyphenanthrene, 4-hydroxyphenanthrene, 9-hydroxyphenanthrene, 1-hydroxypyrene, 6-hydroxychrysene, and 3-hydroxybenzo[a]pyrene were detected in the urinary samples of the coke oven workers by gas chromatography-mass spectrometry. 6 The percentages of samples with metabolites concentrations above the limit of quantification were higher than 90% or nearly 100% (data not shown). For concentrations below the limit of quantification, we used 50% of the limit of quantification in lieu of the specific concentration.…”
Section: Measurements Of Urinary Pah Metabolites and Creatininementioning
confidence: 90%
“…Our previous study has indicated the significantly positive correlation between the urinary PAH metabolites of the coke oven workers and the airborne concentration of total PAHs in different work places, 6 suggesting that the urinary PAH metabolites are good internal biomarkers of PAHs exposure. A comprehensive spectrum of 12 PAHs metabolites, including 1-hydroxynaphthalene, 2-hydroxynaphthalene, 2-hydroxyfluorene, 9-hydroxyfluorene, 1-hydroxyphenanthrene, 2-hydroxyphenanthrene, 3-hydroxyphenanthrene, 4-hydroxyphenanthrene, 9-hydroxyphenanthrene, 1-hydroxypyrene, 6-hydroxychrysene, and 3-hydroxybenzo[a]pyrene were detected in the urinary samples of the coke oven workers by gas chromatography-mass spectrometry.…”
Section: Measurements Of Urinary Pah Metabolites and Creatininementioning
confidence: 91%
See 2 more Smart Citations